Cooperation of chloroplast ascorbate peroxidases and proton gradient regulation 5 is critical for protecting Arabidopsis plants from photo‐oxidative stress. (28th June 2021) - Kameoka, Takashi; Okayasu, Takaya; Kikuraku, Kana; Ogawa, Takahisa; Sawa, Yoshihiro; Yamamoto, Hiroshi; Ishikawa, Takahiro; Maruta, Takanori
Summary: High‐light (HL) stress enhances the production of H2 O2 from the photosynthetic electron transport chain in chloroplasts, potentially causing photo‐oxidative damage. Although stromal and thylakoid membrane‐bound ascorbate peroxidases (sAPX and tAPX, respectively) are major H2 O2 ‐scavenging enzymes in chloroplasts, their knockout mutants do not exhibit a visible phenotype under HL stress. Trans‐thylakoid proton gradient (∆pH)‐dependent mechanisms exist for controlling H2 O2 production from photosynthesis, such as thermal dissipation of light energy and downregulation of electron transfer between photosystems II and I, and these may compensate for the lack of APXs. To test this hypothesis, we focused on a proton gradient regulation 5 ( pgr5 ) mutant, wherein both ∆pH‐dependent mechanisms are impaired, and an Arabidopsis sapx tapx double mutant was crossed with the pgr5 single mutant. The sapx tapx pgr5 triple mutant exhibited extreme sensitivity to HL compared with its parental lines. This phenotype was consistent with cellular redox perturbations and enhanced expression of many oxidative stress‐responsive genes. These findings demonstrate that the PGR5‐dependent mechanisms compensate for chloroplast APXs, and vice versa. An intriguing finding was that the failure of induction of non‐photochemical quenching in pgr5 (because of the limitation in ∆pH formation) was partially recovered in sapx tapx pgr5 . Further genetic studies suggested that this recovery was dependent on the NADH dehydrogenase‐like complex‐dependent pathway for cyclic electron flow around photosystem I. Together with data from the sapx tapx npq4 mutant, we discuss the interrelationship between APXs and ∆pH‐dependent mechanisms under HL stress. Significance Statement: Chloroplast ascorbate peroxidases (APXs) and proton gradient regulation 5 (PGR5) restrict H2 O2 levels under high light by scavenging and by limiting production, respectively, but their functional relationship is largely unknown. Our current genetic study using Arabidopsis plants clearly shows that cooperation between APXs and PGR5 plays a critical role in photoprotection.